Large retroperitoneal mass: A case of an undifferentiated pleomorphic sarcoma - Millennie J. Chen, BS; Shafieh Makehei, MD; Isaac Chen, MD; Simona De Michele, MD; Shiv Bhanu, MD; Justin Wei, MD (Radiology Case Reports)
Soft tissue sarcomas (STS) are a group of rare malignant tumors arising from mesenchymal stem cells. There are more than 60 different types of neoplasms that fall under the umbrella of STS, including tumors that originate from cartilage, adipose tissue, skeletal muscle, or connective tissue, among many other tissue types. One particular type of high-grade aggressive STS is the undifferentiated pleomorphic sarcoma (UPS), formerly known as the malignant fibrous histiocytoma (MFH). There has historically been much debate about the classification and differentiation of UPS from other types of sarcomas, which has only recently been characterized by novel methods of immunohistochemistry markers and sophisticated cytogenetics. This has left much of the literature regarding UPS largely irrelevant in context of our current classification standards.A recent retrospective analysis of 100 UPS cases revealed an incidence of only 9% for UPS originating in the retroperitoneum. We present a case of UPS originating in the retroperitoneum. In this case, a patient suffering from a large right-sided intra-abdominal mass underwent complete surgical resection. We also demonstrate some of the complexities involved in the diagnosis and treatment of a rare retroperitoneal form of UPS.